Model Legal Drafting Penyusunan Peraturan Desa Sebagai Upaya Pengembangan Aturan Perangkat Pemerintahan Desa Campurjo Kecamatan Wonomulyo Kabupaten Polewali Mandar Provinsi Sulawesi Barat - Herman, Herman; Dahri, Irsyad; Muhtar, Muhtar (Peneliti.net, 2023)
The aim of this service activity is to support efforts to improve the quality of village officials in their knowledge of drafting Village Regulations through the Legal Drafting model. To achieve this goal, the activities that will be carried out are conducting socialization and training as well as assistance related to the preparation of village regulations as well as discussion space regarding the preparation of regulations in Campurjo Village, Wonomulyo District, Polewali Mandar Regency. By holding this activity, our hope as a service team is that village officials, in this case the Village Head and Village Representative Body, understand the importance of drafting Village Regulations in assisting the implementation of Village Government. This community service activity uses methods in the form of socialization and skills training through lectures, demonstrations and questions and answers with training participants. Before the material is given, the village service team carries out a free test to find out the extent of the Village Officials' knowledge regarding the preparation of Village Regulations.